Critica, totalità e mediazione. Dalla crisi del marxismo all’ultimo Fortini - Cavazzini, Andrea (L'ospite ingrato, 2021)
The article reconstructs the meaning and the function of the concept of totality in the Marxist twentieth century tradition, and its deconstruction during the “crisis of Marxism” in the late seventies. The positions of the late writings of Fortini are read as a reaction to this crisis and a consciousness of the limits of classical Marxism.